Maternal and neonatal outcome in twin pregnancies at a tertiary care center: a retrospective analysis - Nair, Abhirami; Soni, Anita (International Journal of Research in Medical Sciences, 2025)
Background: Despite many advancements in antenatal health care, twin pregnancies encounter more unfavourable outcomes as multiple pregnancy has always been associated with increased risk of fetomaternal complications in particular prematurity and perinatal morbidity. Rate of twin gestation varies significantly among different societies and geographical region, however with escalating use of assisted reproductive techniques and increased maternal age the incidence of twin gestations is surging. This study was conducted with an objective to analyse the burden of twin gestation along with fetomaternal outcome with any possible associations. Methods: This retrospective observational study conducted in Dr LH Hiranandani Hospital included 51 women with twin pregnancy with gestational age more than 26 weeks, analysed the neonatal and maternal outcome. Results: The incidence of twin pregnancy was 24.24 %, with 68.6 % pregnancies through ART. Gestational Diabetes Mellitus (29.41%) was found to be the most prevailing maternal complication, followed by, PPROM (27.45%). 60.78% of mothers had preterm delivery and lower segment caesarean section was the predominant mode of delivery (94.1%). About 53.1 % babies required NICU admission with prematurity being the most prevalent cause (39.8%) Conclusions: Twin pregnancies warrant systematic follow up for early identification and management of complications. Active supervision with pertinent NICU care can improve fetomaternal outcome.